Assessment of Levels of CRP As A Measure of Stress Response After Open and Laparoscopic Cholecystectomy: Stress Response after Open and Laparoscopic Cholecystectomy - Ahmed Khattak, Imtiaz; Iqbal, Javed; Younis, Sarmad; Aamer Hussain, Syed; Rashid, Zakriya; Shoaib Khan, Mohammad (Pakistan Journal of Health Sciences, 2022)
Laparoscopic cholecystectomy (LC) is supposed to be a first line treatment for complicated bile stones and is regarded as the minimally invasive surgery. Objectives: To determine the levels of CRP as a measure of stress response after open and Laparoscopic cholecystectomy. Methods: A total of 120 patients of both genders aged 20 years or above with fever, abdominal pain, vomiting, nausea and anorexia with symptomatic gall stone were chosen. Laboratory tests, ultrasound and chest radiography were carried out to verify the diagnosis of cholecystectomy and prevent a negative abdomen exploration. The comparison of CRP levels between the two groups was done at 4, 8 and 24 hours. The values ​​of CRP in both procedures were compared with the t-test with P-0.000 taken as significant. Results: The patients mean age was 36.09 ± 8.10 years. There were 50 men and 70 women. Mean CRP was 7.20 ± 2.10 after 4 hours of laparoscopic cholecystectomy; however, after open cholecystectomy, it was 11.30 ± 1.80, CRP after 8 hours in LC was 13.50 ± 7.01 and 21.04 ± 2.14 after open cholecystectomy. The mean CRP levels in laparoscopic cholecystectomy after 24-hrs were 23.40 ± 7.92 and 34.81 ± 7.04 after open cholecystectomy. The most affected age group was 20-35 years in 39(32.5%) patients, 31-50 in 47(39.2%) and 51-65 in 34(28.3%) patients. This study did not find postoperative complications or mortality. Conclusions: CRP is a valuable marker in determining the response to stress in subjects with laparoscopic and open cholecystectomy.